2011 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--17921
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the Foundation for Future Organizational Reform and Transformation at a Large Private University to Expand the Representation of Women Faculty

Abstract: , being the first woman civilian faculty member in her department. Margaret maintains a research program in the area of advanced thermodynamic analyses and health monitoring of energy intensive systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…The Connect Grants framework was informed by two faculty surveys and NSF Indicator Data. Results from the 2009 Faculty Career Satisfaction Survey created and administered as part of an NSF funded self-study project (NSF ADVANCE IT-Catalyst award 0811076 prior to the NSF IT award) identified career navigation as a barrier to the career advancement and leadership role progression of women STEM faculty [7]. Findings from the 2012-2013 Faculty Mentoring Survey administered by the University X Faculty Career Development unit suggested an opportunity for improvement by pairing faculty with mentors that encourage grant proposal submissions and encourage publication authorship [8,9].…”
Section: Background and Rationalementioning
confidence: 99%
“…The Connect Grants framework was informed by two faculty surveys and NSF Indicator Data. Results from the 2009 Faculty Career Satisfaction Survey created and administered as part of an NSF funded self-study project (NSF ADVANCE IT-Catalyst award 0811076 prior to the NSF IT award) identified career navigation as a barrier to the career advancement and leadership role progression of women STEM faculty [7]. Findings from the 2012-2013 Faculty Mentoring Survey administered by the University X Faculty Career Development unit suggested an opportunity for improvement by pairing faculty with mentors that encourage grant proposal submissions and encourage publication authorship [8,9].…”
Section: Background and Rationalementioning
confidence: 99%
“…NSF ADVANCE funded research efforts informed this practice from its inception. As part of the NSF ADVANCE IT-Catalyst funded project, the 2008 faculty climate survey [15] found that with regard to compensation, 62% of women respondents believe that men in their departments receive preferential treatment, while 9% of men respondents believe that women receive preferential treatment. Informed by these internal findings which revealed significant differences in perception regarding salary equity by gender, the upper administration supported RIT Human Resources (HR) and Institutional Research and Policy Studies (IR) to begin conducting annual salary equity studies by gender, rank, discipline for faculty for internal use starting in 2009.…”
Section: Pay Equity Effortsmentioning
confidence: 99%
“…The EFFORT@RIT IT-Catalyst project saw the launch of the faculty salary study conducted by RIT HR and IR that included controls such as department, degree earned, years in rank, terminal degree, gender, and ethnicity. It was found that gender-based average salary gaps existed at each faculty rank within RIT, with women earning about 5% less than their male colleagues [27,28]. Large differences between actual salary and predicted salary were identified and investigated, and salary adjustments began in 2010 to correct for compression and gender-related salary issues [17].…”
Section: Pay Equity Effortsmentioning
confidence: 99%
See 2 more Smart Citations